TWIST1 Gene Variants Cause Craniosynostosis with Limb Abnormalities in Asian Patients - Dhiman, Shalini; Panigrahi, Inusha; Sharma, Maryada; Chaudhry, Chakshu; Garg, Mahak (Journal of Pediatric Genetics, 2023)
The TWIST1 gene codes for a highly conserved transcription factor in a basic helix–loop–helix transcription factors family. The pattern of inheritance is autosomal dominant in Saethre–Chotzen syndrome, Robinow–Sorauf syndrome, and Sweeney–Cox syndrome. Major features of these syndromes include coronal synostosis, vision problems, and deafness, and facial features include hypertelorism, low-set ears, arched eyebrows, beaked nose, maxillary hypoplasia, and other dysmorphisms including broad great toes, clinodactyly, brachydactyly, and cutaneous syndactyly. TWIST1 (bHLH) transcription factor regulates the formation of head and limbs in the embryo. We describe three families affected with craniosynostosis in whom a sporadic TWIST1 variant was identified on whole exome sequencing, chromosomal microarray, and Sanger sequencing.
Keywords: craniosynostosis; craniofacial; SCS; syndactyly; ptosis